Recommendations for post-stroke aphasia rehabilitation: an updated systematic review and evaluation of clinical practice guidelines - Shrubsole, Kirstine; Worrall, Linda; Power, Emma; O'Connor, Denise A (Aphasiology, 2017)
Background: Clinical practice guidelines (CPGs) have been shown to improve patient care and outcomes. For speech pathologists working with people with post-stroke aphasia, there is currently no single high-quality guideline that summarises all of the available research knowledge into recommendations to guide decision-making. While multiple stroke and aphasia guidelines exist, some are of low methodological quality, are out of date, or do not provide recommendations that specifically guide aphasia management. As such, it may be difficult for clinicians to choose one particular guideline to follow. Aim: To identify, extract, and evaluate recommendations from high-quality CPGs to inform the management of post-stroke aphasia by speech pathologists. Methods & Procedures: An updated systematic review of stroke and speech pathology-specific clinical guidelines was conducted in January 2015. The search included multiple databases (MEDLINE, Embase, CINAHL), guideline and stroke websites, and other sources. The quality of included guidelines was assessed using the Appraisal of Guidelines and Research and Evaluation (AGREE) II tool. Guidelines that obtained a high AGREE II "Rigour of Development" score were retained and the aphasia-relevant recommendations from these guidelines were extracted for further analysis. Recommendations were evaluated according to their applicability to aphasia and the clarity of linkages between the recommendations and underlying evidence. Outcomes & Results: Five new guidelines were identified. Their AGREE II ratings ranged from 31.3 to 71.9, and one met the cut-off of 66.67 for further analysis. One hundred and eleven recommendations from four guidelines were extracted and evaluated. From these, 76 recommendations met the inclusion criteria, 25 of which were specifically targeted at aphasia management, the remainder being general rehabilitation principles that may apply to aphasia. Thirty-four recommendations were directly linked to evidence, and 42 were based on consensus. Research gaps were noted for goal-setting, counselling, patient and carer support, and discharge planning, indicating possible areas for future research. There were challenges in comparing recommendations from different CPGs, determining whether evidence was applicable to people with aphasia, and in identifying clear links between the evidence and some recommendations. Conclusions: The collated 76 (34 evidence-based, 42 consensus-based) recommendations can be used by speech pathologists to guide aphasia rehabilitation. Aphasia-specific research is required in areas such as goal-setting, counselling, patient and carer support, and discharge planning.